A Metabolomics Approach Reveals Immunomodulatory Effects of Proteinaceous Molecules Derived From Gut Bacteria Over Human Peripheral Blood Mononuclear Cells - Cambeiro-Pérez, Noelia; Hidalgo-Cantabrana, Claudio; Moro-García, Marco A.; Alonso-Arias, Rebeca; Simal-Gándara, Jesús; Sánchez, Borja; Martínez-Carballo, Elena (Frontiers in Microbiology, 2018)
There are strong evidences that probiotics influence the immune status of the host, in a strain-specific manner, acting in the gastrointestinal tract. On the hypothesis that certain extracellular proteins and peptides from gut bacteria may mediate part of this immunomodulation and assuming they are able to diffuse through the mucus layer and interact with immune cells we have developed this work. Our study attempts to understand the immunomodulatory mechanisms of i) Pext, the extracellular protein fraction of Lactobacillus acidophilus DSM20079T, ii) HM14, a peptide encrypted in an extracellular glycoside hydrolase from Bifidobacterium longum NCIMB 8809 and iii) Escherichia coli O111:B4 lipopolysaccharide (LPS), a well known pro-inflammatory molecule, over human peripheral blood mononuclear cells (PBMCs). An untargeted LC-ESI-QTOF-MS metabolomics approach was applied to reveal intracellular changes in treated-PBMCs isolated from healthy donors. Differences in NADH arrest, NAD+ concentration reduction, as well as increases in palmitic acid and methanephrin were observed in HM14 and Pext treated-cells compared to those stimulated with LPS. This may support an anti-inflammatory molecular mechanism of action of such proteinaceous molecules. Moreover, this methodology has proven the importance of metabolomics approaches to better understanding immune cell responses to gut bacterial-derived molecules.